Applying Value Analysis and Value Engineering to Develop a Popular Wheel Clamp - ALHODIANY, ZAKARYA MOHSEN MUTHANNA (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The work describes the basics of value analysis and value engineering andpresents detailed overview of its distinct stages applicable to any merchandise with the aimof boosting its value. Besides, the paper examines the case of delivering a new popularwheel clamp on the market. The research discovers that one can accomplish it throughimproving the design of a specific model of the device in the framework of value analysisand value engineering. The enhancement consists in reduction of the number ofcomponents, implementation of the fool-proof technology, and taking advantage of theleverage. The activity gives rise to the improved design of an affordable wheel clamp.